Terapeutyczna moc literatury i innych dziedzin sztuki odkrywających sens życia i śmierci - Karkut, Dorota (Dydaktyka Polonistyczna, 2018)
In the article I am taking reflection about the therapeutic value of art. I propose to juxtapose Hans Christian Andersen’s fairy tale The Girl with matches and Eric Emmanuel Schmitt’s book Oskar and Mrs. Rose with artistic expression and therapy through drama. I am paying attention to the subject raised by writers of the death being comforting and freeing. Understanding of this message, thanksto the participation in therapeutic classes, helps to discover the meaning of the life and at the same time allows you to overcome the fear of death and become familiar with its inevitability.